2014
DOI: 10.1016/j.micres.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and enzymatic characterization of glutathione S-transferase from Antarctic sea-ice bacteria Pseudoalteromonas sp. ANT506

Abstract: A glutathione S-transferase (GST) gene from Antarctic sea-ice bacteria Pseudoalteromonas sp. ANT506 (namely PsGST), was cloned and expressed in Escherichia coli. The open reading frame of PsGST comprised 654 bp encoding a protein of 217 amino acids with a calculated molecular size of 24.3 kDa. The rPsGST possesses the conserved amino acid defining the binding sites of glutathione (G-site) and substrate binding pocket (H-site) in GST N_3 family. PsGST was expressed in E. coli and the recombinant PsGST (rPsGST) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
4
22
0
1
Order By: Relevance
“…Furthermore, at 4 °C PhTAC125 is able to grow on 1-Chloro-2,4-Dinitrobenzene (CDNB) that is known to be bound by glutathione S-transferases (GSTs), versatile enzymes playing an important role as detoxifier of exogenous and xenobiotic compounds in many bacteria 42, 43 , including the Antarctic bacteria Pseudoalteromonas sp. ANT506, where GST was shown to be a typical cold active enzyme 44 . Remarkably, two GST-like genes (YibF) are present in the PhTAC125 genome but not in PspTB41.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, at 4 °C PhTAC125 is able to grow on 1-Chloro-2,4-Dinitrobenzene (CDNB) that is known to be bound by glutathione S-transferases (GSTs), versatile enzymes playing an important role as detoxifier of exogenous and xenobiotic compounds in many bacteria 42, 43 , including the Antarctic bacteria Pseudoalteromonas sp. ANT506, where GST was shown to be a typical cold active enzyme 44 . Remarkably, two GST-like genes (YibF) are present in the PhTAC125 genome but not in PspTB41.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, despite most of the genes coding for the enzymes involved in the Glutathione metabolism are shared between PhTAC125 and PspTB41, except for trypanothione synthetase (3.5.1.78) and glutathionyl-spermidine synthase (6.3.1.8), the catabolism of several substrates such as Glutatione (GSH), L-Cysteine, Glycine, Putrescine, L-Ornithine, Spermidine and Spermine is strongly reduced in PspTB41 at 4 °C compared to PhTAC125 (Figure S1). This result indicates that PspTB41 strain is not able to efficiently use such substrates under cold conditions and it might be due to a reduced activity of the enzymes directly involved in the reactions 44 . Interestingly, together to GSH, glutathionylspermidine is likely to be a parallel defense strategy of PhTAC125 against oxidative stress and has been proposed to be more effective at preventing DNA damage induced by free radicals or oxidative species than GSH.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,10 Our earlier studies have revealed that glutathione S-transferase (GST) and SOD play the main roles in the protection mechanism against high salt concentration and low-temperature in the Antarctic bacterium Pseudoalteromonas sp. 11,12 Among other antioxidant enzymes, GPxs are the ubiquitous cytosolic ones, which can catalyze the reduction of H 2 O 2 and other organic peroxides. However, there are few reports about biochemical characterizations of the GPx protein.…”
Section: Introductionmentioning
confidence: 99%
“…Algunas adaptaciones enzimáticas y no enzimáticas descritas en bacterias antárticas son glutatión s-transferasa (Shi et al, 2014), glutatión reductasa (Pugin et al, 2014), tioredoxina (Falasca et al, 2012) catalasas (Tribelli et al, 2012), super óxido dismutasas (Zheng et al, 2006), carotenoides (Dieser et al, 2010) y óxido reductasas (Madonna et al, 2006).…”
Section: Mecanismos De Síntesisunclassified